REALISM AND COMPOSITIONAL REPRESENTATION OF REALITY : AN ANALYSIS OF THE MANIPURI DOCUMENTARY FILM “FRIED FISH CHICKEN SOUP AND A PREMIERE SHOW” - Nepram, Sonia; Khan Thouba, Nawaz (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The debate around realism in documentary cinema has evolved significantly over the years reflecting broader shift in filmmaking techniques, compositional forms, audience expectation, cultural and political contexts. The realms of realism and compositional documentary have been in a constant state of flux, each genre pushing the boundaries of what is considered truth, authenticity, and artistic expression thereby blurring the lines between reality and fiction, and challenging the traditional notions of documentary filmmaking. Several Manipuri documentary films have made endeavors of recreating the reality through their representation on cinematic canvas. Depicting Manipur’s cinematic journey and its socio-political context in a compositional form, the documentary film “Fried Fish, Chicken Soup, and a Premier Show” (2012) relies heavily on editing with found footage and presents an even greater challenge with the inclusion of historical narratives. It intricately combines observational account of a film crew at work during the filming of the Manaobi MM’s Manipuri feature film “21st Century Gee Kunti” (2010) with intertitles, archival footage etc. to depict the history of Manipur. This paper explores the realism and compositional representation of reality in the film which skillfully blends diverse elements to document the trend of change and transformation within the cinematic landscape and the lived reality of Manipuri society in transition.